Análise geoepidemiológica dos óbitos por covid-19 no estado do Maranhão. - OLIVEIRA, Rayanne Alves de (2023)
Mortality from COVID-19 continues to be a serious public health problem, which involves everything from biopsychosocial factors to availability and access to health resources. Continuous efforts have been employed in the development and improvement of vaccines, aiming to control the pandemic. Despite this, the disease continues to cause a high number of deaths. Considering the need to know the epidemiological reality and spatial dynamics of deaths from the disease, the objective was to analyze the geoepidemiological aspects of deaths from COVID-19 reported in the state of Maranhão. This is an ecological study with different analysis measures. Deaths notified by COVID-19, from the Maranhão COVID-19 Notification System, between March 2020 and January 2022 were included. Descriptive statistics of epidemiological variables were performed and to evaluate the association between epidemiological characteristics of cases of COVID-19 and the outcome death, simple and multiple logistic regression models were used, expressing the odds ratios. Monthly mortality rates and the average for the period were calculated by regional health units. Mortality trend analysis was performed using Prais-Winsten regressions. These analyzes were performed using SPSS 24.0 software. In order to spatially distribute the mortality rates, a spatial analysis of the area was carried out and in the spatial autocorrelation analysis, the Global and Local Moran Index (LISA) was used via GeoDa software version 3.16.2. It is also noteworthy that, for spatial analyses, the period was decomposed into first, second and post second wave of COVID-19. Thematic maps were created in QGIS 3.22.7. Research approved by the Research Ethics Committee of the Federal University of Maranhão, under opinion no 4,227,396. A total of 10,986 deaths were identified, among which the highest frequency occurred in people aged 60 years and over, men, brown race/skin color, with laboratory diagnostic criteria, who underwent a rapid test, attended at a public health unit, and who they had comorbidities, with emphasis on systemic arterial hypertension and diabetes mellitus. The risk factors for mortality were male gender, age from 30 years old, having performed an RT-PCR exam, diagnostic criteria by imaging exam (tomography), having one or more associated comorbidities. The three with the greatest association were respectively diabetes mellitus, neurological diseases and obesity, respiratory and renal diseases and systemic arterial hypertension were also associated with deaths. Mortality rates ranged from 0.0 to 44.60 deaths/100,000 inhabitants, especially in the regions of São Luís and Imperatriz. Considering the average, the rates were higher in the period of the second wave, and the spatial distribution was heterogeneous in all waves. The mortality trend remained stationary in the 19 health regions in the investigated period. The global Moran index indicated a positive spatial correlation of mortality rates in the three periods. The local Moran analysis showed statistically significant clusters of deaths, mainly in the West region. Such findings raise the need to expand surveillance actions and implement control measures, aiming to mitigate mortality from COVID-19. Furthermore, it is considered that the western region of the state is a priority area for these interventions.